Realizing low voltage-driven bright and stable quantum dot light-emitting diodes through energy landscape flattening - Yiting Liu; Yingying Sun; Xiaohan Yan; Bo Li; Lei Wang; Jianshun Li; Jiahui Sun; Yaqi Guo; Weipeng Liu; Binbin Hu; Qingli Lin; Fengjia Fan; et al. (Light: Science & Applications)
Abstract Solution-processed quantum dot light-emitting diodes (QLEDs) hold great potential as competitive candidates for display and lighting applications. However, the serious energy disorder between the quantum dots (QDs) and hole transport layer (HTL) makes it challenging to achieve high-performance devices at lower voltage ranges. Here, we introduce “giant” fully alloy CdZnSe/ZnSeS core/shell QDs (size ~ 19 nm) as the emitting layer to build high-efficient and stable QLEDs. The synthesized CdZnSe-based QDs reveal a decreased ground-state band splitting, shallow valence band maximum, and improved quasi-Fermi level splitting, which effectively flatten the energy landscape between the QD layer and hole transport layer. The higher electron concentration and accelerated hole injection significantly promote the carrier radiative recombination dynamics. Consequently, CdZnSe-based device exhibits a high power conversion efficiency (PCE) of 27.3% and an ultra-low efficiency roll-off, with a high external quantum efficiency (EQE) exceeding 25% over a wide range of low driving voltages (1.8-3.0 V) and low heat generation. The record-high luminance levels of 1,400 and 8,600 cd m-2 are achieved at bandgap voltages of 100% and 120%, respectively. Meanwhile, These LEDs show an unprecedented operation lifetime T95 (time for the luminance to decrease to 95%) of 72,968 h at 1,000 cd m-2. Our work points to a novel path to flatten energy landscape at the QD-related interface for solution-processed photoelectronic devices.